The Influence of Problem-Based Learning Model on Heat and Its Transfer Topic Toward Junior High School Students’ Problem-Solving Skills - Aprilia, Agnes Verena; Parmin, Parmin; Wusqo, Indah Urwatin (Unnes Science Education Journal, 2020)
This study intends to reveal the influence of PBL on heat and its transfer topic toward the students' problem-solving skills and scientific attitudes. The design of this study was quasi-experimental with the nonequivalent control group. The samples consisted of the students of VII A (experimental class) and VII B (control class) selected using a purposive sampling technique. Data were collected through observation and tests. The results showed that the value of the correlation coefficient obtained based on the posttest of students' problem-solving skills was r = 0.728. Moreover, the t-test analysis on the value of the correlation coefficient of problem solving skill scored t count = 6.58, which indicated the existence of a dependent influence or relationship. The significance of the effect was seen from the coefficient of determination score of 56.25%. Besides, there were 75% of the students gave a positive response to the learning process. Thus, it concludes that the PBL on heat and its transfer topic has affected the students' problem-solving skills.